2022
DOI: 10.3389/fonc.2022.849626
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT-based radiomics analysis may help to predict neoadjuvant chemotherapy outcomes in breast cancer

Abstract: BackgroundThe aim of this study was to evaluate the clinical usefulness of radiomics signature-derived 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography–computed tomography (PET-CT) for the early prediction of neoadjuvant chemotherapy (NAC) outcomes in patients with (BC).MethodsA total of 124 patients with BC who underwent pretreatment PET-CT scanning and received NAC between December 2016 and August 2019 were studied. The dataset was randomly assigned in a 7:3 ratio to either the training or valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…From the IMH features reported in the reviewed literature, 11,20,22,23,26,28,29 an association with prediction of response to NAST was suggested for coefficient of variation, 11 skewness, 11 QRobust mean absolute deviation 29 and kurtosis. 26 The other analysed IMH features (in particular entropy, range, standard deviation, uniformity, variance and SUVmean/SUVmax ratio) were not considered to be associated with response to NAST in any study.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…From the IMH features reported in the reviewed literature, 11,20,22,23,26,28,29 an association with prediction of response to NAST was suggested for coefficient of variation, 11 skewness, 11 QRobust mean absolute deviation 29 and kurtosis. 26 The other analysed IMH features (in particular entropy, range, standard deviation, uniformity, variance and SUVmean/SUVmax ratio) were not considered to be associated with response to NAST in any study.…”
Section: Resultsmentioning
confidence: 97%
“…Table 3 shows the results of the analysis of texture-based features in the prediction of response to NAST. From the reviewed literature, the majority of the studies (Ha et al, 11 Molina-García et al, 19 Yoon et al, 20 Lee et al, 21 Li et al, 22 Roy et al, 29 Umutlu et al 25 and Yang et al 26 ) suggested FDG PET texture-based features may predict response to NAST. However, none of the predictive texture-based features was the same in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Primarily, pathologic images and clinicopathologic parameters alone provide only limited information in predicting pCR. If multimodal data are added, such as ultrasound ( Cui et al, 2021 ), CT ( Moghadas-Dastjerdi et al, 2021 ), MRI ( Huang et al, 2023 ; Shi et al, 2023 ), PET-CT ( Yang et al, 2022 ) examination data, or even genetic testing data, the predictive efficacy of the model can be further improved and the uncertainty of model application can be reduced. Secondly, the number of enrolled cases and the number of clinicopathologic features also affect the uncertainty of model application.…”
Section: Discussionmentioning
confidence: 99%